miR-424 Promotes Bovine Adipogenesis Through an Unconventional Post-Transcriptional Regulation of STK11 - Wang, Li; Zhang, Song; Zhang, Wenzhen; Cheng, Gong; Khan, Rajwali; Junjvlieke, Zainaguli; Li, Shijun; Zan, Linsen (Frontiers in Genetics, 2020)
Adipose tissue is the largest energy reservoir and secretory organ in the animal body, and is essential for maintaining normal physiological functions and metabolic balance. MicroRNAs regulate the process of adipogenic differentiation through post-transcriptional regulatory mechanisms. In the present study, miR-424 was upregulated during bovine adipocyte differentiation both in vivo and in vitro. The overexpression and interference of miR-424 exhibited the positive regulatory role in the differentiation of bovine adipocytes. Furthermore, miR-424 directly binds to the three prime untranslated region (3' UTR) of serine/threonine kinase 11 (STK11, also called LKB1), a master upstream gene in the AMP-activated protein kinase (AMPK) cascade, and up-regulates its expression. Functional studies showed that the knockdown of STK11 attenuated the pro-adipogenic effect of miR-424. Post-transcriptional regulation of STK11 by miR-424 was mediated potentially in an RNA binding protein (RBP) binding site-dependent manner. In conclusion, our study shows that miR-424 promotes bovine adipogenesis through an unconventional post-transcriptional regulation of STK11, which may serve as a potential target for the regulation of bovine adipogenesis and the improvement of livestock breeding efficiency.